A Mathematical Analysis of a Model Involving an Integrable Equation for Wave Packet Envelope - Kaplan, Melike; Akbulut, Arzu (Wiley, 2022)
This study investigates new optical solutions to a model with an integrable equation for wave packet envelopes. For this purpose, we have employed two reliable techniques involving the modified extended tanh function and the exponential rational function procedures. We have also given the 3D graphics of the obtained solutions.
Keywords: QA1-939; Mathematics